Effect of Make a Match Learning Model Towards Learning Result of Students Cross Interest about Human Reproduction System Material in Social Science Class Grade XI - Nisa Al Mukarromah; Ristiono Ristiono; Zulyusri Zulyusri; Indra Hartanto (Bioeducation Journal, 2019)
Cross-interest is a curricular program that is provided to accommodate the expansion of students' interests, talents, and academic abilities with a mastery orientation of a group of scholarly subjects beyond the choice of interests. Selection of cross-interest subjects at SMAN 1 Pasaman is determined by the school. Based on daily test result on cell materials in class XI IPS, it is known that there are still many students who have not get the minimum completeness criteria. Implementation of make a match learning model is an attempt to overcome the problem. This study aims to determine the effect of applying make-match learning model to the learning outcomes of students cross-interest about reproduction system human material class XI IPS in SMAN 1 Pasaman. This research is a quasi experimental by using Non-Randomized Control Group Posttest Only Design. The population in this study is all students of Class XI IPS in SMAN 1 Pasaman. Samples were taken using Purposive Sampling technique. In this study Class XI IPS 5 as experimental class and class XI IPS 2 as a control class. The instrument used is the final test of multiple choice questions as much as 20 items. The result of t test is known that t-value> t-table (3.51> 1.67). Therefore, the hypothesis is stated acceptable. So it can be concluded that the application of make a match learning model gives a positive influence on the learning outcomes of learners cross-interest about reproduction system material in human class XI IPS in SMAN 1 Pasaman.